Stabilisation of Nanosilver Supramolecular Hydrogels with Trisodium Citrate - Joanna Kowalczuk; Oleg M. Demchuk; Mariusz Borkowski; Michał Bielejewski (Molecules)
Designing supramolecular gelators with targeted properties is very difficult and mainly relies on structural modifications of known gelator molecules. However, very often, even minor modifications can result in the complete loss of gelation capabilities. In the present work, we have studied the influence and role of the silver nanoparticles (AgNPs) and trisodium citrate (TSC) additives on the self-assembly process of alanine derivative gelator (C12Ala) and intermolecular interactions resulting in hydrogel systems of enhanced stability and sustainability. The effect of phase separation and diversity of supramolecular microstructures of gelator internal matrix on the composition of the investigated tricomponent system was studied thoroughly with thermal analysis methods (TGA/DSC), high-resolution nuclear magnetic resonance spectroscopy (HR-MAS NMR), and polarising optical microscopy (POM). The molecular mechanism of gelation and the interactions responsible for enhanced properties of nanosilver hydrogels was determined and described, indicating the synergistic role of TSC and AgNPs in the self-assembly process.